Chemical, biological, and pharmacological evaluation of the aqueous extract of Ilex paraguariensis, St. Hill. (Aquifoliaceae) (Research, Society and Development, 2022)
This study aimed to quantify the total phenolic and flavonoid contents in the aqueous extract of Ilex paraguariensis (EIP) and investigate its antioxidant, antimicrobial, antiulcerogenic, and antidepressant properties with concomitant verification of its effects on relevant biochemical parameters using in vivo models. EIP has in its composition 236.28 ± 11.83 mg GAE/g of total phenolics and 44.07 ± 5.56 mg QE/g of total flavonoids, corroborating its antioxidant activity. Antimicrobial assays against gram-positive (Staphylococcus aureus and Enterococcus faecalis) and gram-negative bacteria (Escherichia coli e Pseudomonas aeruginosa) showed a promising activity of EIP. The EIP administered at 500 and 1000 mg/kg doses prevented the development of gastric ulcers induced in rats following immobilization at 4 °C, however, in the ethanol-induced ulcers no significant effects were observed up to a dose of 1000 mg/kg. Gastric secretion and total acidity index in pylorus-ligated rats were reduced after treatment with EIP, and the pH did not change significantly compared to the control in the tested model. Administration of EIP to mice (250, 500, and 1000 mg/kg) significantly altered the barbiturate-induced sleep time and results of the tail suspension and forced swim test. Repeated doses of EIP did not significantly alter the evaluated biochemical markers (blood glucose, urea, creatinine, triglycerides, and total cholesterol). The results indicate that EIP may relieve gastrointestinal disorders by reducing acid secretion and decreasing immobility time in mice, suggesting an antidepressant effect. Notably, administration of multiple doses of EIP was considered preliminarily safe.